REVIEW ARTIKEL: AKTIVITAS ANTIBAKTERI SENYAWA METABOLIT SEKUNDER PADA BEBERAPA EKSTRAK TANAMAN TERHADAP BAKTERI Escherichia coli - Ripaldy Apriansya; Rudi Kartika; Shaparuddin Nur Arifullah; Dilo Jhosea Luciano Eduardo; Muhammad Raihan Aswat; Muhammad Adhitya Rizkirullah (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Indonesia's current biodiversity makes it something valuable for the community. Especially the use of plants that are used as medicinal materials. This is supported by the content of secondary metabolite compounds found in plants such as flavonoids, phenolics, steroids, saponins, tannins and others. These compounds have antibacterial activity that can be used to inhibit the growth of microbes that harm humans. By conducting a literature study of 10 national and international articles in the last 10 years of publication to review the ability of several plants that have potential as antibacterials. Tests were carried out on Escherichia coli bacteria which included the extract solvent used, the content of metabolite compounds in the extract and its activity based on the inhibition zone diameter value and/or minimum inhibitory concentration (MIC). Keywords: Antibacterial, inhibition zone diameter, Escherichia coli, minimum inhibitory concentration, secondary metabolites